Effect Of Li2co3 Addition On The Piezoelectric And Dielectric Properties Of Pb0.93la0.02sr0.05(Zr0.52ti0.48)O3 Ceramics - Siddiqui, Maliha (2016)
Lead zirconate titanate (PZT) is the most widely investigated amongst lead-based perovskite ceramics. Its piezoelectric and dielectric properties are always modified with different dopants. When PZT doped with La3+ and Sr2+, the piezoelectric constant (d33) and dielectric constant (εr) are increase with slightly increase in electromechanical coupling factor (kp). However, high kp and εr is desirable for electromechanical devices such as piezoelectric fan. In this research Pb0.93La0.02Sr0.05(Zr0.52Ti0.48)O3 (PLSZT) ceramic is doped with Li2CO3 to investigate its effect on piezoelectric and dielectric properties. The ceramic was synthesized by high energy planetary ball milling in air for 40 hours and sintered at relatively low temperatures from 1150 °C to 850 °C for 3 hour, respectively. The addition of Li2CO3 in PLSZT improved the densification of the ceramics and increases the average grain size. Thus, piezoelectric and dielectric properties are enhanced with the increase of Li+ content. The best piezoelectric and dielectric properties were obtained for 0.7 mol% Li+ doped PLSZT ceramics. The density is 7.420 g/cm3, kp is 0.461, d33 is 259 pC/N, εr is 1270, and tan δ is 0.084 is observed.